2022
DOI: 10.1371/journal.pone.0275108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure characterization analysis and molecular model construction of anthracite

Abstract: Coal is the largest non-renewable energy as well as an important basic energy and industrial raw material. Thus, correctly understanding the molecular structure characteristics of coal has important theoretical value for realizing carbon neutralization. In this work, we clarified the molecular structure characteristics of anthracite, where the organic matter in anthracite was characterized and analyzed by industrial/elemental analysis, FTIR, XPS, XRD and solid 13C NMR. The ratio of bridge carbon to the perimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Chen et al conducted the CP/MAS 13 C NMR experiments using model coal compounds and fitted a nonlinear regression equation to calibrate the apparent carbon fraction, which was initially validated by Bian et al when constructing a molecular model of medium-rank coal. Nevertheless, to date, there are still numerous studies on coal molecular modeling without any modifications when using the results from the peak fitting of the CP/MAS 13 C NMR spectra. Few studies have systematically reported the influencing mechanism and a comparison between these corrections. In conclusion, more efforts are required to optimize or verify the analytical methods for the CP/MAS 13 C NMR spectroscopy of coal.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al conducted the CP/MAS 13 C NMR experiments using model coal compounds and fitted a nonlinear regression equation to calibrate the apparent carbon fraction, which was initially validated by Bian et al when constructing a molecular model of medium-rank coal. Nevertheless, to date, there are still numerous studies on coal molecular modeling without any modifications when using the results from the peak fitting of the CP/MAS 13 C NMR spectra. Few studies have systematically reported the influencing mechanism and a comparison between these corrections. In conclusion, more efforts are required to optimize or verify the analytical methods for the CP/MAS 13 C NMR spectroscopy of coal.…”
Section: Introductionmentioning
confidence: 99%
“…Niekerk and Mathews 21 proposed an improved method for constructing macromolecular models of coal by means of various experiments including ultimate analysis and nuclear magnetic resonance, and further established the molecular structure model of lignite by conducting experiments and quantum chemical calculations. Jia et al 22 built the molecular structure model of anthracite from the Yangquan mining area based on information including the composition of functional groups, the structure of carbon skeletons, and the composition of surface elements, and then verified the rationality of the model.…”
Section: ■ Introductionmentioning
confidence: 99%